2022
DOI: 10.1186/s12871-022-01787-2
|View full text |Cite
|
Sign up to set email alerts
|

The Pericapsular Nerve Group (PENG) block combined with Local Infiltration Analgesia (LIA) compared to placebo and LIA in hip arthroplasty surgery: a multi-center double-blinded randomized-controlled trial

Abstract: Background The PEricapsular Nerve Group (PENG) block is a novel regional analgesia technique that provides improved analgesia in patients undergoing hip surgery while preserving motor function. In this study the PENG block was investigated for analgesia in elective total hip arthroplasty (THA). Methods In this multi-centre double-blinded randomized-controlled trial, in addition to spinal anesthesia and local infiltration analgesia (LIA), THA patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 31 publications
2
51
0
2
Order By: Relevance
“…In the present research, the quadriceps muscle strength was similar between the PENG block group and the sham block group after surgery, and the ranges of quadriceps muscle activity and "time to first walk" were even significantly better in the PENG group (8,9,29). The exercise retention effect enables patients to move early after surgery, which in itself is associated with fewer complications, shorter hospital stays, and lower mortality (30,31).…”
Section: Discussionsupporting
confidence: 51%
“…In the present research, the quadriceps muscle strength was similar between the PENG block group and the sham block group after surgery, and the ranges of quadriceps muscle activity and "time to first walk" were even significantly better in the PENG group (8,9,29). The exercise retention effect enables patients to move early after surgery, which in itself is associated with fewer complications, shorter hospital stays, and lower mortality (30,31).…”
Section: Discussionsupporting
confidence: 51%
“…The complete text of the remaining 21 articles was read to determine eligibility. Sixteen additional articles were then excluded due to reasons listed as follows: they were reviews or case reports ( n = 6) [ 14 19 ] or retrospective studies ( n = 3) [ 20 22 ], or the comparison was with other forms of nerve block, and not FICB ( n = 4) [ 23 26 ], or the comparison was with placebo ( n = 3) [ 27 29 ]. Finally, five studies [ 10 12 , 30 , 31 ] were selected for our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Zheng et al 2022 [23] and Lin et al 2022 [24] found no significant variance among total hip arthroplasty patients who had an intra-articular local anaesthetic injection and those who received a placebo injection (20 ml saline) when they compared the two methods. Cases in the PENG group had noticeably lower pain levels than those in the control group during recuperation, however this difference disappeared after patients were sent home.…”
Section: Discussionmentioning
confidence: 99%